2021
DOI: 10.4254/wjh.v13.i6.662
|View full text |Cite
|
Sign up to set email alerts
|

Role of chromosome 1q copy number variation in hepatocellular carcinoma

Abstract: Chromosome 1q often has been observed to be amplified in hepatocellular carcinoma. This review summarizes literature reports of multiple genes that have been proposed as possible 1q amplification drivers. These largely fall within 1q21-1q23. In addition, publicly available copy number alteration data from The Cancer Genome Atlas project were used to identify additional candidate genes involved in carcinogenesis. The most frequent location for gene amplification was 1q22, consistent with the results of the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 63 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…We also found several significant alterations of molecular characteristics between HRisk and LRisk groups. Common somatic changes include mutations p53 and beta-catenin are frequently detected repeatedly in HCC, resulting in activation of the Wnt signaling pathway and dysregulation of the cell cycle, respectively ( Jacobs and Norton, 2021 ). TP53 is the most frequently mutated in HCC, and patients with TP53 mutations had a poorer prognosis compared with patients with wild-type TP53 ( Villanueva and Hoshida, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found several significant alterations of molecular characteristics between HRisk and LRisk groups. Common somatic changes include mutations p53 and beta-catenin are frequently detected repeatedly in HCC, resulting in activation of the Wnt signaling pathway and dysregulation of the cell cycle, respectively ( Jacobs and Norton, 2021 ). TP53 is the most frequently mutated in HCC, and patients with TP53 mutations had a poorer prognosis compared with patients with wild-type TP53 ( Villanueva and Hoshida, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Along with mutations, chromosomal abnormalities are frequent genetic events in HCC ( Schulze et al, 2016 ). In particular, broad genomic deletions have been noted for 1p, 4q, 6q, 8p, 13q, 16p, and 17q and gains for 1q, 6p, 8q, 17q, and 20q ( Jacobs and Norton, 2021 ). We found that HRisk had significantly higher copy number alterations than LRisk, suggesting that HRisk existed a deeper degree of chromosomal instability.…”
Section: Discussionmentioning
confidence: 99%